Purification and activation of the double-stranded RNA-dependent eIF-2 kinase DAI. - Kostura, M (1989)
The double-stranded RNA (dsRNA)-dependent protein kinase DAI (also termed dsI and P1) possesses two kinase activities; one is an autophosphorylation activity, and the other phosphorylates initiation factor eIF-2. We purified the enzyme, in a latent form, to near homogeneity from interferon-treated human 293 cells. The purified enzyme consisted of a single polypeptide subunit of approximately 70,000 daltons, retained its dependence on dsRNA for activation, and was sensitive to inhibition by adenovirus VA RNAI. Autophosphorylation required a suitable concentration of dsRNA and was second order with respect to DAI concentration, which suggests an intermolecular mechanism in which one DAI molecule phosphorylates a neighboring molecule. Once autophosphorylated, the enzyme could phosphorylate eIF-2 but seemed unable to phosphorylate other DAI molecules, which implies a change in substrate specificity upon activation. VA RNAI blocked autophosphorylation and activation but permitted the activated enzyme to phosphorylate eIF-2. VA RNAI also blocked the binding of dsRNA to the enzyme. The data are consistent with a model in which activation requires the interaction of two molecules of DAI with dsRNA, followed by intermolecular autophosphorylation of the latent enzyme. VA RNAI would block activation by preventing the interaction between DAI and dsRNA.